Przekształcenia praktyk zarządzania w urzędach administracji samorządowej - Szumowski, Witold (Transformations of the management practice in the self-government administration, 2005)
Transformations of the management practice is not connected to the business sector only. Currently, the changes of the ways of managing concern to public organizations in the comparable degree. The present article describes the changes of the ways of managing in the self-government offices, with particular consideration of the process management. Also, the author depicts the results of the research he carried out, which relate to the application of the processal approach in the Lower Silesian self-government administration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 350-358